Mengungkap Kisah Songket Sukarara - Pranata, Putu Gede Yudha; Harparorrazikin, Habib; Ramadhani, Nikmatul Maula; Kusuma, Wanda Savira; Lestari, Ayu Novia; Atrujia, Baiq Sriyana Hijjah; Adrian, Abdul Halim; Sasmita, M.Tanggap; Hizmi, Surayyal (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
This study aims to enhance the digital marketing capabilities of Bahri Artshop, a traditional Songket weaving business located in Sukarara, Lombok. Despite its strong local reputation, the business struggles to utilize digital platforms effectively for product promotion. Prompted by inquiries from potential buyers during university exhibitions about the absence of a website and social media accounts, the research team stepped in to assist in platform development. The research highlights the cultural narratives embedded in each unique weaving motif created by Bahri Artshop. The qualitative study involved discussions with the business owner, Hana, and her family, alongside training sessions for workers on content creation, photography, and website management. Findings indicate that the implementation of a website and Instagram account has notably improved brand awareness and strengthened the shop's position within the digital marketplace. These results underscore the vital role of mentoring and education in supporting SMEs in entering broader digital markets.